2020
DOI: 10.3892/mmr.2020.10977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined treatment with PD‑L1 Ig and CD40L mAb on immune tolerance in the CBA/J x DBA/2 mouse model

Abstract: The embryo is a natural allograft and is the only exception to immune rejection, which reflects maternal immune tolerance towards the embryo. However, pregnancy loss is primarily caused by maternal immune rejection of the embryo. The aim of the present study was to explore the effects of combined treatment of programmed death-ligand 1 (Pd-l1) immunoglobulin (ig) and cd40-ligand (cd40l) monoclonal antibody (mab) on immune tolerance in an abortion-prone mating model. Mice were divided into the normal, spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…By engaging the P2X7 receptor, ATP subsequently induces the release of pro-inflammatory cytokines by monocytes, macrophages, and microglia, resulting in the death of retinal endothelial cells [ 129 , 130 ]. Additionally, CD40 participates in the pathological process of autoimmune, and anti-CD40 monoclonal antibodies can lead to immune tolerance [ 131 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…By engaging the P2X7 receptor, ATP subsequently induces the release of pro-inflammatory cytokines by monocytes, macrophages, and microglia, resulting in the death of retinal endothelial cells [ 129 , 130 ]. Additionally, CD40 participates in the pathological process of autoimmune, and anti-CD40 monoclonal antibodies can lead to immune tolerance [ 131 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CBA mouse strain has a reproductive phenotype that is currently characterized as fetal "resorption," describing a fetal loss pathology with a dark necrotic fetal tissue mass at an implantation site (44,45). Many studies have demonstrated that immune interventions, such as maternal injections of cytokines, adjuvants, or blocking antibodies alter the rates of fetal loss in CBA mice (46)(47)(48)(49)(50)(51). Prior studies have also performed adoptive transfers of Tregs from a variety of sources to decrease rates of CBA fetal loss (21, 44,[52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%